Atomic Level Dissection of the Platelet Endothelial Cell Adhesion Molecule 1 (PECAM-1) Homophilic Binding Interface: Implications for Endothelial Cell Barrier Function. Issue 2 (February 2022) - Liao, Danying; Sundlov, Jesse; Zhu, Jieqing; Mei, Heng; Hu, Yu; Newman, Debra K.; Newman, Peter J.
Abstract : Objective: PECAM-1 (platelet endothelial cell adhesion molecule 1) is a 130 kDa member of the immunoglobulin (Ig) gene superfamily that is expressed on the surfaces of platelets and leukocytes and concentrated at the intercellular junctions of confluent endothelial cell monolayers. PECAM-1 Ig domains 1 and 2 (IgD1 and IgD2) engage in homophilic interactions that support a host of vascular functions, including support of leukocyte transendothelial migration and the maintenance of endothelial junctional integrity. The recently solved crystal structure of PECAM-1 IgD1 and IgD2 revealed a number of intermolecular interfaces predicted to play important roles in stabilizing PECAM-1/PECAM-1 homophilic interactions and in formation and maintenance of endothelial cell-cell contacts. We sought to determine whether the protein interfaces implicated in the crystal structure reflect physiologically important interactions. Approach and Results: We assessed the impact of single amino acid substitutions at the interfaces between opposing PECAM-1 molecules on homophilic binding and endothelial cell function. Substitution of key residues within the IgD1-IgD1 and IgD1-IgD2 interfaces but not those within the smaller IgD2-IgD2 interface, markedly disrupted PECAM-1 homophilic binding and its downstream effector functions, including the ability of PECAM-1 to localize at endothelial cell-cell borders, mediate the formation of endothelial tubes, and restore endothelial barrier integrity. Conclusions: Taken together, these results validate the recently described PECAM-1 IgD1/IgD2 crystal structure by demonstrating that specific residues visualized within the IgD1-IgD1 and IgD1-IgD2 interfaces of opposing molecules in the crystal are required for functionally important homophilic interactions. This information can now be exploited to modulate functions of PECAM-1 in vivo. Abstract : Supplemental Digital Content is available in the text.